The end of organised crime in the European Union - Dorn, Nicholas (Crime, law and social change, 2009)
So much has been written - and vigorously contested - about ‘organised crime’ (OC) that the impending fall of this familiar icon may come as a shock, both to its detractors and to those who take it for granted. Yet that moment may be upon us, for reasons that this paper will explore, as the European Union shifts the vocabulary within which policies on police cooperation are articulated. A pivot of this change is the EU Council Decision on Europol, first debated by the Council in late 2006 and anticipated as applying from 2010 onwards. This will shift the scope of Europol’s work from ‘organised crime’ (attributing qualities to criminality) to ‘serious crime’ (concern with impacts and harms falling on individual and collective victims); will transfer financing of Europol to the Community budget; and so will initiate parliamentary scrutiny. These issues in security governance are explored from ‘northern’, ‘southern’ and ‘eastern’ European perspectives and in the contexts of ongoing enlargement and democratisation of the EU.